Targeted detection for XY disorders of sex development - WANG NAN; ZHU WENJIAO; CHENG TONG; ZHU HUI; ZHAO SHUANGXIA; HAN BING; WANG HAO; SONG HUAIDONG; QIAO JIE (2019)
The invention provides targeted detection for XY disorders of sex development, in particular to use of genes associated with disorders of sex development or loci of the genes, and/or detection reagents for the genes or the loci, for preparing a reagent or a kit, wherein the reagent or the kit is used for detecting the susceptibility of a subject to the disorders of sex development, and the genes associated with the disorders of sex development are selected from the group consisting of SRD5A2, AR and NR5A1. 本发明提供了一种针对XY性发育异常疾病的靶向检测，具体地，本发明提供性发育异常相关基因或其位点、和/或其检测试剂的用途，用于制备试剂或试剂盒，所述试剂或试剂盒用于检测被检测对象对性发育异常的易感性，所述性发育异常相关基因选自下组：SRD5A2、AR和NR5A1。